The Effect Of The Realıstıc Mathematıcs Educatıon Model On Problem-Solvıng Abılıty And Responsıbılıty Character Of Elementary School Students - Febrianti, Intan Fajrin; Rosidah, Cholifah Tur; Rusminati, Susi Hermin (Jurnal Elementaria Edukasia, 2024)
This study aims to analyze the effect of the Realistic Mathematics Education model on elementary school students’ problem-solving ability and character of responsibility. The background of this study stems from the low level of students’ problem-solving performance and the need to strengthen character values within mathematics learning. The Realistic Mathematics Education model is selected because it provides contextual learning experiences that allow students to build understanding through real situations. This research employs a quantitative approach with a quasi-experimental design, specifically a pretest–posttest control group design. The subjects consist of fourth-grade students divided into a Realistic Mathematics Education learning group and a conventional learning group. Data are collected through a problem-solving ability test and a responsibility character questionnaire that have been validated and tested for reliability. The results indicate a significant difference between the two groups in both variables. Students taught using the Realistic Mathematics Education model demonstrate greater improvement compared to those who receive conventional instruction. The multivariate analysis confirms that the Realistic Mathematics Education model has a significant simultaneous effect on both research variables. These findings suggest that context-based mathematics instruction enhances thinking skills while fostering positive character development simultaneously. This study concludes that the Realistic Mathematics Education model is a practical approach for integrating cognitive development and character formation in elementary school mathematics learning.